2021
DOI: 10.5902/2179769243156
|View full text |Cite
|
Sign up to set email alerts
|

Meditação: uma estratégia de cuidado em saúde para estudantes universitários

Abstract: Objetivos: desenvolver atividades meditativas com estudantes de uma universidade do noroeste gaúcho e analisar a percepção de estudantes universitários sobre a prática meditativa. Método: pesquisa-intervenção, de abordagem qualitativa. Realizaram-se 11 encontros para meditação, com participação de cinco estudantes, no período de abril a julho de 2019. Os dados produzidos mediante questionário com dados sociodemográficos e de saúde, observação não participante e entrevista aberta foram submetidos à análise temá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
1
0
6
Order By: Relevance
“…Consequently, mediation would have a direct impact on their quality of life since concentration and memory were highlighted as one of the products of continuous practice. In a more recent publication carried out with college students in Brazil (Schuh, et al, 2021), all reported data proved that mindfulness meditation provided increased levels of concentration and focus for studying, improved sleep quality, promoted self-knowledge and subjective well-being after the sample participated in 11 sessions of the practice. Additionally, they also reported lower intensity on their anxiety, stress, and depression.…”
Section: Resultsmentioning
confidence: 88%
“…Consequently, mediation would have a direct impact on their quality of life since concentration and memory were highlighted as one of the products of continuous practice. In a more recent publication carried out with college students in Brazil (Schuh, et al, 2021), all reported data proved that mindfulness meditation provided increased levels of concentration and focus for studying, improved sleep quality, promoted self-knowledge and subjective well-being after the sample participated in 11 sessions of the practice. Additionally, they also reported lower intensity on their anxiety, stress, and depression.…”
Section: Resultsmentioning
confidence: 88%
“…Hortência e Camélia relataram que a pouca experiência delas com práticas de meditação foi disponibilizada pelas suas escolas médicas. Isso reflete o movimento de preocupação que as escolas vêm dando 33,34 , cada vez mais, ao sofrimento mental e ao adoecimento psíquico do seu corpo discente. Silveira et al 34 relatam os efeitos positivos de um programa de prática de No caso específico da formação médica, a técnica abordada neste estudo se baseia no cuidado destinado ao profissional médico ainda no estágio de formação, de modo a atuar para que ele descristalize conservas culturais há muito estabelecidas e a abrir o caminho para uma sociedade de bem-estar.…”
Section: Resultsunclassified
“…Ressalta-se a importância da inclusão das PICS na formação profissional para a promoção da saúde (SCHUH et al, 2021). A TCI é uma prática legitimamente brasileira e já está presente em mais de 25 países.…”
Section: Resultsunclassified